Photon attenuation properties of samariumdoped zinc bismuth silicate glass: A studyusing Cs-137, Co-60, and Na-22 RadiationSources (CaJoST, 2024)
The linear attenuation coefficient (LAC) of the ZBSS series was investigated, revealing a strong dependence on density and composition. ZBSS10, with the highest density (6.89 g/cm3) and Bi2O3 weight fraction (0.931 wt%), exhibited the highest LAC (2.829 cm-1) at 0.284 MeV. The increased density and Bi2O3 content enhance photon interactions, leading to higher attenuation. However, LAC decreases with increasing photon energy, as higher-energy photons penetrate deeper into the material. The MFP increases as Bi2O3 content decreases, allowing photons to travel farther before interacting with atoms. At 0.284 MeV, ZBSS10 (0.931 wt% Bi2O3) had the shortest MFP (0.353 cm), while ZBSS50 (0.741 wt% Bi2O3) had an MFP of 0.455 cm, representing a 28.9% increase. Similarly, at 2.506 MeV, ZBSS50 had a larger MFP. Increasing SiO2 content enhances neutron absorption, leading to improved shielding performance. ZBSS50, with its highest SiO2 content and lowest Bi2O3 content, exhibits the highest fast neutron effective removal cross section, surpassing other materials in the series, except for steel magnetite (SM). ZBSS10 and ZBSS50 are exceptional shielding for photon and neutron compared to some standard neutron-absorbing materials making them an ideal material for radiation protection applications, including nuclear facilities and medical radiation therapy.